Pro-inflammatory diets promote the formation of hyperuricemia - Liu, Xin; Chen, Ting-Yu; Gao, Teng-Yu; Shi, Ke-Qin; Yin, Fu-Qiang; Yu, Yun-Xiang; Zhang, Chao (Frontiers in Endocrinology, 2024)
Background: Hyperuricemia, as a very prevalent chronic metabolic disease with increasing prevalence year by year, poses a significant burden on individual patients as well as on the global health care and disease burden, and there is growing evidence that it is associated with other underlying diseases such as hypertension and cardiovascular disease. The association between hyperuricemia and dietary inflammatory index (DII) scores was investigated in this study. Methods: This study enrolled 13, 040 adult subjects (aged ≥ 20 years) from the US National Health and Nutrition Survey from 2003 to 2018. The inflammatory potential of the diet was assessed by the DII score, and logistic regression was performed to evaluate the relationship between the DII score and the development of hyperuricemia; subgroup analyses were used to discuss the influence of other factors on the relationship. Results: Participants in the other quartiles had an increased risk of hyperuricemia compared to those in the lowest quartile of DII scores. Stratification analyses stratified by body mass index (BMI), sex, hypertension, drinking, diabetes, education level and albumin-creatinine-ratio (ACR) revealed that the DII score was also associated with the risk of hyperuricemia (P<0.05). There was an interaction in subgroup analysis stratified by sex, age, and hypertension (P for interaction <0.05). The results showed a linear-like relationship between DII and hyperuricemia, with a relatively low risk of developing hyperuricemia at lower DII scores and an increased risk of developing hyperuricemia as DII scores increased. Conclusions: This study showed that the risk of hyperuricemia increased at slightly higher DII scores (i.e., with pro-inflammatory diets), but not significantly at lower levels (i.e., with anti-inflammatory diets). The contribution of the DII score to the development of hyperuricemia increased with higher scores. The relationship between inflammatory diets and hyperuricemia requires more research on inflammation, and this study alerts the public that pro-inflammatory diets may increase the risk of developing hyperuricemia.